Impacts of an earn-a-bike cycling education program on children's time spent cycling. (March 2020) - Carlson, Jordan A.; Steel, Chelsea; Bejarano, Carolina; Grimes, Amanda; Shook, Robin P.; Reddy, Ashleigh; Green, Maggie; Morefield, Thomas; Steele, Laura; Campbell, Karen; Rogers, Eric
Abstract: Background: Cycling is a source of physical activity that is feasible and beneficial to health, yet is underutilized by youth in many countries. Bike gifting and education programs are sometimes delivered to youth to support cycling. This study aimed to assess impacts of a bike education program that involved earning a bike (called Earn-a-Bike) on children's time spent cycling and attitudes and perceptions of cycling. Methods: The Earn-a-Bike program was delivered after school to 38 5th graders living in low-income urban communities, at three different schools. Participants wore global positioning systems (GPS) trackers to provide objective measurements of time spent cycling before and after the program. Participants also completed a pre and post survey and parents completed a post survey on perceptions and attitudes. Statistical models tested changes in time spent cycling and survey responses. Results: Time spent cycling increased from 12.4 to 21.5 min per week (68% increase; F[1, 23.7] = 6.49; p = .018), with similar increases observed between boys and girls and across schools. 59% of trips occurred on the weekends and 27% occurred in the evenings on weekdays, and student survey data corroborated this information. Students reported that the top reasons they participated in the program were to learn about bike safety (66.7%) and to learn how to take care of a bike (66.7%). Parents had positive attitudes/perceptions of the program (85–100% agreement with positive statements). Conclusions: Bike education programs that result in the child earning a bike appear promising for increasing the currently low rates of cycling and active transportation in youth, though multilevel strategies are likely needed to support larger increases in cycling. Highlights: A cycling education program was delivered during existing afterschool programs. The program included cycling safety, bike maintenance, and earning a bike. Time spent cycling was objectively assessed with global positioning systems. Time spent cycling increased by 68% from before to after the program. Such programs are promising for complementing built environment and policy changes.